2007
DOI: 10.1099/jmm.0.46893-0
|View full text |Cite
|
Sign up to set email alerts
|

AIDS-related opportunistic mycoses seen in a tertiary care hospital in North India

Abstract: Sixty symptomatic confirmed human immunodeficiency virus (HIV)-positive adult patients, of both sexes, suspected of having a fungal infection were taken as a study population, and the clinicomycological profile was correlated with the immunological status of the patients with particular reference to CD4 counts. Relevant samples were collected and subjected to direct microscopy, fungal culture and serology. CD4 counts were determined by flow cytometry. Patients belonged to the age group of 17-65 years, with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
40
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 12 publications
(10 reference statements)
10
40
1
Order By: Relevance
“…Infections of lower respiratory tract with Cryptococcus in HIV positive cases indicate a lowered CD 4 counts which were not performed in the study due to lack of facilities which is a limitation of our study. Findings of our study correlate with the findings of Anupriya Wadhwa et al 15 39 cases of invasive pulmonary aspergillosis were confirmed clinically and radiologically. Aspergillus niger from 32 and flavus from 7 cases was isolated.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Infections of lower respiratory tract with Cryptococcus in HIV positive cases indicate a lowered CD 4 counts which were not performed in the study due to lack of facilities which is a limitation of our study. Findings of our study correlate with the findings of Anupriya Wadhwa et al 15 39 cases of invasive pulmonary aspergillosis were confirmed clinically and radiologically. Aspergillus niger from 32 and flavus from 7 cases was isolated.…”
Section: Discussionsupporting
confidence: 81%
“…Findings of our study are on par with findings of Kaur et al, 1992, Kumar & Goyal, 2001 and Anupriya Wadhwa et al [13][14][15] Heterosexual mode of transmission was the commonest (73.5%) mostly from males to females, followed by blood transfusion (11%), drug abuse (2.5%) and in 13% of cases, cause could not be ascertained. In the present study, out of total 287 specimens processed for isolation of pathogens, 266 produced polymicrobial growth and 21 did not demonstrate any significant pathogens which may be due to viral or bacterial or fungal which could not be cultivated.…”
Section: Resultssupporting
confidence: 61%
“…Among the pulmonary infections in HIV-infected patients, the most common pathogens found are Mycobacterium tuberculosis, Pneumocystis jirovecii, and Cryptococcus species P jerovecii and Cryptococcus neoformans pulmonary coinfection has been infrequenty reported, while there have been few reports only of Cryptococcus and Mycobacterium coinfection from India. [7][8][9] Respiratory infection due to Candida species has been sporadically reported from India, 10 but it is difficult to differentiate between Candida colonization and infection. We are presenting here an HIV-positive patient with pulmonary tuberculosis, Pneumocystis jirovecii pneumonia, Cryptococcus neoformans pneumonia, and meningitis along with Candidiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous involvement is reported in nearly 10% of human immunodeficiency virus (HIV)-associated histoplasmosis cases [2]. Histoplasmosis has been increasingly reported from India in the past few years and most of the cases are found to be associated with HIV infection [1][2][3][4][5]. Cutaneous involvement is not the manifestation commonly found in the reports from India.…”
Section: Introductionmentioning
confidence: 95%